Предности на минимално инвазивниот хируршки третман на фрактурите на capitullum radii со примена на ЕСИН методот - Камилоски, Марјан (Медицински факултет, УКИМ, Скопје, 2018)
In childhood fractures of the proximal part of the radius typically involve the neck of the radius, representing 5-10% of the injuries in the elbow at this age. Most commonly they occur after the development of proximal radial epiphysis after 5 years of age. Proximal radius fractures are epiphysiolysis of the head of the radius including all types according to the Salter Harris classification and metaphyseal fractures on the neck of the radius. The treatment of radial neck fractures in children varies depending on the degree of dislocation, angulation and bone marrow maturity. The aim of this study was to determine an adequate surgical treatment of proximal fractures of the radius in childhood, which will provide the best functional results, short hospitalization and return to everyday activities. In this retrospective-prospective study, we present our results obtained in 80 patients with head and neck fracture treated at the Children's Surgical Clinic in the period from 2010 to 2015. We used two surgical techniques: open reposition and transcondylar fixation - in 41 patients, closed reposition and retrograde intramedullary nailing ESIN method by Metaizeau – in 39 patients. All inclusion and exclusion criteria of patients were met in this study. The indication for surgical treatment was based on the Judet classification system. The age of the patients was 5.5-14.5 years (mean age 10.02/9.89 years in two groups), of which 52 were male and 28 female children. According to the analyzed parameters with regard to the mechanism of injury, 43 patients were injured in a fall from height, 12 patients in a car accident and 25 patients had sport injury. Forty-nine (49) children had type III and 31 type IV fractures according to the Judet classification system. Children treated with the method of closed reposition and percutaneous fixation showed a shorter operating time, shorter hospitalization, shorter rehabilitation time and better functional results.
Докторска дисертација одбранета во 2018 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Славчо Стојменски.
Keywords: radial neck and head fractures, children